KONSTRUKSI SISTEM EKONOMI ISLAM PEMIKIRAN TOKOH EKONOMI ISLAM KONTEMPORER (ABU AâLA AL-MAUDUDI, BAQIR ASH-SADR, DAN ADIWARMAN A. KARIM) - Amarudin, Muchamat (LIPI, 2018)
In contemporary times, various Islamic economic ideas emerged like Abu Ala Al-Maududi, Baqir Ash-Sadr, and Adiwarman Azwar Karim. The emergence of Thought and School of Modern Islamic Economics. In the modernist era, Islamic economics began to be knit back to be raised as a concept of theoretical and applicative science. The division of the school of thought of Islamic Economics appears in three schools. The School of Baqir As Sadr, the Mainstrem and the Alternative Madzah, the background of the division of these three schools is the disagreement on the concept of what and how the Islamic economy. However, it is not yet certain that the application of Islamic economic concepts and theories in todays society is sufficiently shaded by the three schools. Efforts to re-emergence of Islamic economics amid the world community with the conceptual offer of science and economic system that seemed to only begin to be pursued massively since the modernist century, especially as has happened in Indonesia, Islamic economics has been massive since the emergence of sharia banking activities in Indonesia pioneered by Bank Muamalat Indonesia.